Portable Aquaponic Model for Household and Agricultural Applications (International Journal of Scientific Research in Science and Technology, 2025)
Food and water shortages, pesticide contamination, and limited agricultural land pose significant challenges to organic food production. A small-scale aquaponic system offers a sustainable solution by integrating fish and vegetable farming in a closed-loop, water-efficient system. However, existing models often require high investment, technical expertise, and large space, making them less accessible. This study develops a cost-effective, portable aquaponic model using locally available materials. Over 45 days, the system maintained stable water quality, supporting fish and plant growth. Tilapia (Oreochromis mossambicus) grew to an average of 31.5 g (0.5 g/day), while spinach (Spinacia oleracea) yielded 1960 g in 10 sq. ft., demonstrating its potential for sustainable food production. Future research should focus on optimizing feeding strategies and water quality management to enhance fish growth rates, exploring alternative, locally sourced fish feed options for better sustainability, and integrating renewable energy sources, automation, and advanced nutrient recycling to improve efficiency.